Cellular forces and matrix assembly coordinate fibrous tissue repair - Mahmut Selman Sakar (Nature Portfolio, 2016)
Planar in vitromodels for wound closure stress the role of lamellipodial protrusions and purse-string contraction. Here the authors develop a 3D biomimetic model for tissue repair and show a mode of stromal closure that relies on whole tissue deformations, cell migration and matrix deposition.